An International Survey of Animals in Schools: Exploring What Sorts of Schools Involve What Sorts of Animals, and Educators’ Rationales for These Practices - Helen Lewis (People and Animals: The International Journal of Research and Practice, 2022)
Over recent decades, the use of animal-assisted interventions (AAIs) in educational settings has attracted growing international interest both among educators and the research community. However, there has been little comparative analysis of the demographics of participants and the rationale behind such practices. The aim of this paper is to address this. An anonymous online questionnaire was distributed via social media and other networks. Quanti-tative and qualitative data were collected from 610 participants across 23 countries, mostly from the United Kingdom and North America. In total, 315 (51.6%) participants reported involving animals in their settings. The results show that although animals featured from preschool to adult education contexts, the primary school years (5–11) accounted for 60% of responses. More than 30 different species were reported, with dogs being the most popular. The overriding reason educators give for involving animals is the perception that they make an important contribution to children’s well-being. Practices around the involvement of dogs provide a focus for discussion. The research breaks new ground in highlighting commonalities and contrasts in school demographics associated with the involvement of animals across a range of international contexts. It also points to a consensus around the perceived well-being benefits for children of such interventions. For practitioners, the paper has value in prompting reflection on the need for a clear rationale before embarking on such an intervention, and highlights practical considerations needed before bringing an animal into an educational setting. The paper also suggests potential areas for future research, relating to possible benefits for and agency of the animals who are involved.